RDB2RDF: A relational to RDF plug‐in for Eclipse. (10th August 2012) - Marx, Edgard; Salas, Percy; Breitman, Karin; Viterbo, José; Casanova, Marco Antonio; Bishop, Judith; Notkin, David
SUMMARY The process of transforming data stored in relational databases (RDBs) into sets of Resource Description Framework (RDF) triples is known as triplification or RDB2RDF. It consists of two consecutive operations, schema extraction and data conversion. Schema extraction is a process similar to creating an external schema, and contains a collection of database views. The data conversion is divided into two steps. The first step consists of deciding how to represent database schema concepts in terms of RDF classes and properties, defining an RDB2RDF mapping. The second step consists of the actual conversion of relational data to RDF data instances, based on the mapping previously defined. Although the schema extraction is very well understood, the data conversion operation is still murky. Indeed, the World Wide Web Consortium RDB2RDF Working Group has been working to define a standard language, called R2RML, to describe RDB2RDF mapping files. The definition of the R2RML, however, is still undergoing changes. In this paper, we introduce an Eclipse plug‐in that supports the entire conversion process. Its architecture takes into consideration the specificities of the triplification process by providing a modular structure that encapsulates the stable and well‐understood components separately from the volatile, change‐prone mapping strategies. The latter are accessible via a well‐defined interface to promote information hiding and separation of concerns and to facilitate evolution. Copyright © 2012 John Wiley & Sons, Ltd.